القلب المكاني في معجم تهذيب اللغة وعلاقة معانيه والاستفادة منه في تعليم اللغة العربية لغير الناطقين بها - Putri Wahyu Rizkiani (Rayah Al-Islam, 2018)
Al-Qolbu Al-Makani (Metathesis is the transpositition of sounds or letters in a word) in Tahdzib Al-Lughoh is the fluctuation of the letters in Arabic words by presenting forward or backword which does not result in the change of meaning. This is the linguistic development that is occurred through the times and the changing of the Arab generations that resulted the different pronunciation of the words from one tribe to the others that produced a new word whose characters and meaning were identical.The study was then intended to reveal the volatility of Al-Af’al Al-Mahmuzah (verb that contain the letter of hamzah (أ)and therelationship of the meanings of these words, and to learn to benefit from these contractions in Arabic instruction in the teaching of vocabulary in particular. This study used the qualitative opproach, which was an analytical description, i.e. the way the study was collected, the analysis of the flipping in Tahdzib Al-Lughoh dictionary and then the meaning of the words inverted. The collected data were then verified analytically that it can show the relationship of the meaning of those words. The outcome of this study was highlighted as follows: 1)Al-Qolbu Al-Makani in Al-Af’al Al-Mahmuzah are marginalized in Tahdzib Al-Lughoh of like other chapters, but it was included in chapters of Al-Lafif or Al-Ajwaf. 2) The relationship between the meanings of the words reflected in Al-Qolbu Al-Makani is carried one meaning, which was indicated of the inclusion by Ibnu Jinni in his book as Mukhoshos. 3) The application of metathesis in teaching Arabic to non-Arabic speakers by using the vocabulary in the sentences.